Digital Animasi 2 Dimensi Dengan Metode Cell Shadding Dan Rigging Bone Studi Kasus : Legenda Gunung Tugel - Fendi Aji Purnomo; Eko Harry Pratisto; Agus Purnomo; Ahzan Saiful Huda; Ady Setyo Nugroho (Universitas Sebelas Maret, 2017)
Mature Indonesian culture is now diminishing. Indonesian society, increasingly popular by the outside culture through the development of increasingly sophisticated technology. One is the story of a growing legend in their respective regions, so it becomes ironic as children today are uncertain of not caring about their own culture. One of the growing legend stories is